Question order effects in sustainable behavior norm measurement: Gender differences - Poškus, Mykolas Simas; Sadauskaitė, Raimonda (Psichologija, 2015)
Sustainable behavior is an important and increasingly popular field of research, but the question order effects that may occur in descriptive and injunctive sustainable behavior norm measurements remain largely unexplored. Even less attention is drawn to gender differences that may be present in question order effects. In the present study, we have investigated the question order effects and their gender differences in measurements of descriptive and injunctive social norms directed at sustainable behavior. For the purposes of the study, three questionnaires were constructed, each questionnaire consisting of 16 items half of which were directed at injunctive and half at descriptive social norms. The questionnaires differed only in the order in which the items were presented. Engineering, art, and social science students from various Lithuanian universities participated in the study (N = 296). The participants were equally distributed by gender, their mean age was 20 years (SD = 1.5). Participants were asked to fill in the questionnaires during lectures, and each participant was randomly assigned to fill in one of three types of questionnaires. The results have shown that the evaluations of injunctive and descriptive social norms were sensitive to the question order. When priming participants with one type of social norm, the evaluation of the other type of social norm was affected. Presenting questionnaire items in random order did not cancel priming; rather, it made both types of social norms salient at the same time, and therefore norm measurements of this group did not differ from those that were obtained under priming. The further analysis indicated that the question order effects were present only in the female sample. We recommend presenting questionnaire items directed at descriptive and injunctive social norms in random order. When measuring just one type of social norm, we would recommend adding items directed at the other type of social norm as well, in order to obtain data that would be more comparable with other studies.
Keywords: order effects; sustainability norms; questionnaire design; gender differences